2022
DOI: 10.3390/jcm11144062
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Reduction of STIC Acquisition Time for Volumetric Assessment of the Fetal Heart—Benefits and Limitations of Semiautomatic Fetal Intelligent Navigation Echocardiography (FINE) Static Mode

Abstract: (1) Objective: To scrutinize the reliability and the clinical value of routinely used fetal intelligent navigation echocardiography (FINE) static mode (5DHeartStatic™) for accelerated semiautomatic volumetric assessment of the normal fetal heart. (2) Methods: In this study, a total of 296 second and third trimester fetuses were examined by targeted ultrasound. Spatiotemporal image correlation (STIC) volumes of the fetal heart were acquired for further volumetric assessment. In addition, all fetal hearts were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In 95.9% (twin 1) and 93.9% (twin 2), at least 7 cardiac planes were correctly reconstructed. These results are consistent with those derived from previous studies [ 11 , 23 , 24 , 30 , 34 , 35 ]. In our past studies, FINE showed overall depiction rates between 83.3% and 96.9%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In 95.9% (twin 1) and 93.9% (twin 2), at least 7 cardiac planes were correctly reconstructed. These results are consistent with those derived from previous studies [ 11 , 23 , 24 , 30 , 34 , 35 ]. In our past studies, FINE showed overall depiction rates between 83.3% and 96.9%.…”
Section: Discussionsupporting
confidence: 93%
“…The static mode allows the automatic generation of the nine diagnostic planes using fast-acquired STIC volumes (e.g., 1s). The FINE standard mode reconstructed at least 7 planes in 96.9%, while the FINE static mode did so in 94.2% [ 35 ]. According to that, we concluded the possible usefulness of the FINE static mode in moving fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the heart's position as well as the fetal cardiac axis is essential to facilitate accurate diagnosis and planning further management or interventions. An abnormal cardiac axis can be associated with CHD, and the likelihood of an abnormal cardiac axis depends on the CHD type [20,21].…”
Section: Introductionmentioning
confidence: 99%